Pengaruh Variasi Konsentrasi Manitol-Sukrosa Sebagai Bahan Pengisi Pada Formulasi Tablet Hisap Terhadap Sifat Fisik Sediaan - Salsabilla Dhiya Atik Nuraini; Fitria Ayu Kusumaningtyas; Rahma Dwi Novitasari; Abdullah Syafiq Ahmadi; Nandiyyah Atikah; Shabrina Putri Arianti; Dewi Rahmawati; Yani Ambari (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
This article discusses the effect of variations in the concentration of mannitol-sucrose as a filler in the formulation of antioxidant lozenges from various plant extracts on the physical properties of the preparation. Lozenges are preparations that can contain active substances with additional ingredients and sweeteners that dissolve in the mouth. The use of mannitol and sucrose as additional ingredients in lozenges provides advantages such as sweet taste and ease of use. The aim of this study is to find the optimal ratio between mannitol and sucrose to obtain good physical properties of lozenges. The research method used is a literature review article (LRA) by accessing information sources from databases such as Google Scholar and PubMed. The results showed that variations in mannitol-sucrose concentration affected the physical properties of lozenges, such as weight uniformity, hardness, friability, and tablet disintegration time. Thus, choosing the right ratio between mannitol and sucrose is important to produce quality lozenges.